Effect of the anchoring group in the performance of carbazole-phenothiazine dyads for dye-sensitized solar cells. (February 2015) - Gupta, Kankatala S.V.; Zhang, Ji; Marotta, Gabriele; Reddy, Marri Anil; Singh, Surya Prakash; Islam, Ashraful; Han, Liyuan; De Angelis, Filippo; Chandrasekharam, Malapaka; Pastore, Mariachiara
Abstract: A combined experimental and theoretical study is carried out on two novel carbazole-phenothiazine dyadic dyes bearing the simple carboxylic acid and the more rarely investigated malonic acid as anchoring group. An improvement of the photovoltaic performances is observed when the malonic acid is employed in place of the carboxylic acid, even if the highest efficiencies for this family of organic dyes were recorded with the use of the cyanoacrylic and rhodanine-3-aceti acid as anchoring units. The low photocurrents measured in the case of the carboxylic anchoring are rationalized on the basis of the computational modelling of the isolated dye in solution as well as the investigation of the electronic structure of extended dye-sensitized TiO2 models. The theoretical calculations suggest that the low short current densities might arise from the unfavourable interplay of the dye's optical properties (blue shift of the absorption spectrum) and of the energy alignment between the dye's LUMO and the semiconductor conduction band edge, possibly causing an inefficient electron injection process. Highlights: The effect of the anchoring group substitution was investigated in a series of dyadic carbazole-phenothiazine dyes. The anchoring group remarkably affects the cell performances with conversion efficiencies going from 2.4% to 5.8%. The malonic acid anchoring yielded lower efficiencies than those of the rhodanine-3-acetic and cyanocarylic acid groups. The malonic acid anchoring showed better performances when compared to the carboxylic acid anchoring.